2019
DOI: 10.1080/21681376.2019.1701543
|View full text |Cite
|
Sign up to set email alerts
|

Regionalizing the infrastructure turn: a research agenda

Abstract: An interdisciplinary 'infrastructure turn' has emerged over the past 20 years that disputes the concept of urban infrastructure as a staid or neutral set of physical artefacts. Responding to the increased conceptual, geographical and political importance of infrastructureand endemic issues of access, expertise and governance that the varied provision of infrastructures can causethis intervention asserts the significance of applying a regional perspective to the infrastructure turn. This paper forwards a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 87 publications
1
27
0
3
Order By: Relevance
“…Efforts to study critical infrastructure and its conditioning of politics can be found moving in and out of labels like critical infrastructure studies, extrastatecraft, and stacktivism (Larkin, 2013;Springett, 2013;Amin, 2014;Easterling, 2014;Anand, 2017), but have remained mostly outside the remit of political theory, despite a turn to infrastructure in fields like geography and urban studies (Dodson, 2017;Addie et al, 2020). These labels connote different varieties of interest in political action centered on the infrastructural supports that make possible specific political, social, and material realities.…”
Section: Critical Infrastructure and Its Historiesmentioning
confidence: 99%
“…Efforts to study critical infrastructure and its conditioning of politics can be found moving in and out of labels like critical infrastructure studies, extrastatecraft, and stacktivism (Larkin, 2013;Springett, 2013;Amin, 2014;Easterling, 2014;Anand, 2017), but have remained mostly outside the remit of political theory, despite a turn to infrastructure in fields like geography and urban studies (Dodson, 2017;Addie et al, 2020). These labels connote different varieties of interest in political action centered on the infrastructural supports that make possible specific political, social, and material realities.…”
Section: Critical Infrastructure and Its Historiesmentioning
confidence: 99%
“…Therefore, for 'innovative finance' we are looking at possible future financing solutions that suit new requirements, whether known or unknown. Hence, different geographical and temporal contexts in applying existing solutions could potentially be innovativeespecially if there are more effective products, processes, services, technologies or business models for markets, governments and society (Addie et al, 2020;Cantafio & Ryan, 2020;Ersoy, 2017;Ersoy & Alberto, 2019).…”
Section: Literature Review: Infrastructure Funding and Finance As Innovation?mentioning
confidence: 99%
“…Ao inserirmos esses condomínios na discussão das infraestruturas, nos cabe tratar de um ponto chave na literatura decorrente do 'infraestructure turn' (Addie, Glass & Nelles 2020) das últimas décadas: a falha. Como portadoras de progresso e desenvolvimento, as infraestruturas são, desde sua concepção, acompanhadas de expectativas e promessas.…”
Section: Sob a Lente Das Infraestruturasunclassified
“…As infraestruturas que esses empreendimentos trazem são a evidência física desses processos (Larkin 2013) e disputas, tanto na busca por elas quanto em suas falhas. A reflexão aqui proposta visa contribuir tanto para o estudo das infraestruturas urbanas quanto para a ideia de pensar nelas em termos regionais (Addie, Glass & Nelles 2020), assim como produzir material empírico para ampliar o estudo de modo de vida de elites e do fenômeno das gated communitites para outras cidades do 'sul global', permitindo um estudo global dos processos de transformações urbanas e de produção da cidade.…”
Section: Considerações Finaisunclassified